Advanced breast cancer education for cancer nurses: A systematic review. (October 2022) - Drury, Amanda; Dowling, Maura; Diez de los Rios de la Serna, Celia; Erdem, Sema; Aroyo, Violet; Wiseman, Theresa; Bağçivan, Gülcan
Abstract: Background: Access to comprehensive, integrated, multidisciplinary care is one of the most urgent and actionable recommendations of the Advanced Breast Cancer Global Alliance. However, access to specialist breast care units, and specialist breast cancer nurses is variable, influenced by access to specialist education and role recognition. To date, there has not been a synthesis of evidence regarding educational programmes related to advanced breast cancer education for nurses. Objectives: The aim of this review was to determine the content, mode of delivery, assessment and outcomes of education programmes related to advanced breast cancer for nurses. Review methods: A systematic review was undertaken, according to the Joanna Briggs Institute's mixed methods review methodology. Data sources: MEDLINE, PUBMED, CINAHL, Scopus, PsycInfo, Joanna Briggs Institute, Web of Science and grey literature sources were systematically searched. Eleven publications met the inclusion criteria. Data relating to programme content, mode of delivery, assessment and outcomes were extracted and analysed. Results: This review identifies a limited number of educational programmes within this specialist area of nursing practice. Shortcomings in the development, implementation and evaluation of advanced breast cancer education programmes included limited use of educational standards, theoretical frameworks and patient and public involvement to inform programme development. Evaluation of education programmes related to advanced breast cancer relied predominantly on self-reported learning, with limited consideration of the impacts of education on service delivery, patient experience or quality of care. Conclusions: Future development of advanced breast cancer education programmes must consider the alignment of programme content and learning outcomes with existing educational and competency standards. Evaluation of educational programmes in this field must endeavour to enhance rigour of methods, incorporating standardised questionnaires, and multiple methods and sources of data to evaluate the broader impacts of advanced breast cancer education for nurses.